Pengaruh Model Pembelajaran Generatif Terhadap Kemampuan Berpikir Kritis Matematis Siswa - Simanjuntak, Parulian; Suharyati, Suharyati (Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
. The purpose of this study was to determine the effect of Generative learning models on students' mathematical critical thinking skills in quadratic connection material. The research method used is the experimental method, with a sample of 30 students, using simple random sampling techniques, and techniques for retrieving data sourced from library documents and giving essay tests and data analysis techniques using the t-test. In the normality test using the Liliefors test and homogeneity test using the Fisher test, it was concluded that the data were nomal and homogeneous. In the homogeneity test obtained Fcount (1,072) <Ftable (1.86). In testing the hypothesis by using the t-test obtained tcount (5.96)> t table (2.00), so it can be said that there is a significant effect of the Generative learning model on students' mathematical critical thinking abilities. This shows that the Generative learning model influences students' critical thinking skills mathematically.